Observasi praktik public relation pada usaha laundry di Kota Malang - Mawarni, Mega (Maliki Interdisciplinary Journal, 2023)
In the current era of globalization, information technology has progressed very rapidly. This has an impact on all aspects of human life. People’s daily lives will become easier with technological advances which have an impact on many aspects of human life. Business process activities are one of them. Business is an important element in meeting human needs and is a component of economic activity. The individual and social level of human life is influenced by business operations. The purpose of writing this article is to present the results of observations in public relations practices at New Daily Laundry Malang which were carried out directly at the laundry location. The data collection technique is carried out by observing, namely to obtain information about human behavior that occurs in reality and to find out the truth of science. Carrying out interview techniques, documentation, and practicing how to serve customers directly.